Phage Specificity of the Freshwater Fish Pathogen Flavobacterium columnare - Laanto, Elina (American Society for Microbiology, 2011)
Flavobacteria and their phages were isolated from Finnish freshwaters and fish farms. Emphasis was placed on finding phages infecting the fish pathogen Flavobacterium columnare for use as phage therapy agents. The host ranges of the flavobacterial phages varied, phages infecting F. columnare being more host specific than the other phages.